Le document, parent pauvre de la donnée. À la recherche du fonds d'archives perdu - Barbier, Jonathan; Mandret-Degeilh, Antoine (Anuarul Institutului de Istorie A.D. Xenopol - Iaşi, 2024)
This article aims to understand the evolution, in France, of the meanings of the word “document” in archival science and in the human and social sciences. How did the document, a term which refers to very different media such as a paper writing, a film, a photograph or even a digital file, make its entry into French legislation in the second half of the 20th century and was it competed by other expressions like “data”?
Keywords: Données; Histoire des archives et de l’archivistique; Unité archivistique

Lettres patentes de louis XV portant nomination d'un archiviste des domaines de Versailles et Marly - H. Lemoine (Gazette des archives, 1937)